Human migration and population structure 2 - Novembre, John (Henry Stewart Talks, 2015)
Coalescent-based tools for studying population structure, Admixture proportion inference, Principal components analysis, Tree-based models of population structure, Visualizing allele frequency distributions, Major inferences from population structure in humans